A Philosophical Dictionary, Volume 01 - Voltaire, 1694-1778; Leigh, Oliver Herbrand Gordon; Morley, John, 1838-1923; Smollett, T. (Tobias), 1721-1771; Fleming, William F. (Salt Lake City, UT : Project Gutenberg, 2011)
"A Philosophical Dictionary, Volume 01" by Voltaire is an encyclopedic dictionary published in 1764. This alphabetically arranged work criticizes religious institutions and established authorities through pointed, often provocative articles. Beginning as a dinner party game, it evolved into Voltaire's lifelong project$1 (Ba portable, affordable collection designed to educate and challenge readers. The dictionary champions tolerance, freedom of press, and reason while attacking what Voltaire saw as fanaticism. Though burned by authorities across Europe, it became wildly popular with the public and enlightened rulers alike. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Dictionnaire_philosophique
Release date is 2011-03-28
Produced by Andrea Ball, Christine Bell & Marc D'Hooghe (From images generously made available by the Internet Archive.)
Keywords: Philosophy -- Dictionaries; Criticism (Philosophy)